Growth performance and digestibility in exocrine pancreatic insufficient pigs supplemented with a pancreatic enzyme preparation - Donaldson, Janine (My University, 2009)
Exocrine pancreatic insufficiency (EPI) is a major complication of cystic fibrosis. Conventional treatment involves the replacement of pancreatic enzymes and intake of a low fat diet. However, contrary to previous therapeutic strategies, a high fat diet may be beneficial in EPI patients. The present study investigated the effects of dietary supplementation with Creon 10 000 a pancreatic enzyme preparation, in conjunction with a high-fat diet, on growth performance, digestibility and absorption of fat in a pig model of EPI by the surgical ligation of the pancreatic duct in 6 male pigs (Swedish Landrace X Yorkshire X Hampshire). Following surgery, and for the duration of the experimental period, pigs were fed a high fat diet (twice daily). The experimental period lasted for 15 days during which blood, urine and faecal samples were collected. In the last 7 days of the experimental period (days 8-14), Creon 10 000 was included in the high fat meals. Urine and faecal samples were analysed for dry matter, crude protein and fat content. Plasma was used to assess the lipaemic index and the plasma lipid profiles. Treatment with Creon 10 000 significantly increased body mass (P = 0.016) and the digestibility of dry matter, crude protein as well as the co-efficient of fat absorption were also significantly improved following treatment (P<0.05). Creon 10 000 improved the lipaemic index values and significant changes in plasma free fatty acid and triglyceride concentrations were observed but not in cholesterol or high and low density lipoproteins. This study supports previous reports that the administration of pancreatic enzyme preparations together with a high fat meal is a beneficial strategy for the nutritional management of EPI.
Keywords: Exocrine pancreatic insufficiency; pigs; growth; digestibility; high-fat diet